Correlation between Spirituality Levels and Coping Mechanism among First-Year Students in Health Science Programs - Fitriani, Dwi Rahmah; Nabila, Nabila; Milkhatun, Milkhatun (Inspirasi Foundation, 2025)
Introduction: Spirituality plays an important role in influencing an individual's ability to manage stress and challenges, including among students in health-related fields. The level of spirituality reflects the depth of a person's spiritual beliefs, practices, and experiences, which may be linked to coping mechanisms. Objective: This study aims to determine the relationship between the level of spirituality and coping mechanisms among freshmens in the Health Study Program at Universitas Muhammadiyah Kalimantan Timur. Methods: This research employed a quantitative method with a descriptive approach. The population consisted of freshmens enrolled in the Health Study Program. Data were collected using validated questionnaires and analyzed using the Spearman Rank correlation test. Results: The majority of respondents were 18 years old (69.7%), female (81.2%), Muslim (98.9%), and from the Public Health undergraduate program (30.0%). Most respondents had a high level of spirituality (59.0%), while 41.0% had a moderate level. Regarding coping mechanisms, 57.9% used adaptive coping, while 42.1% employed maladaptive coping. The Spearman Rank test yielded a p-value of 0.000 (≤0.005), indicating a statistically significant relationship. The correlation coefficient was 0.238, demonstrating a weak but positive correlation between spirituality levels and coping mechanisms. Conclusion: There is a significant positive relationship between the level of spirituality and coping mechanisms among freshmens in the Health Study Program, although the strength of the correlation is weak. These findings highlight the potential importance of spiritual development in enhancing students' coping strategies.